Digital Citizenship In Civic Education Learning: A Systematic Literature Review - Fajri, Iwan; Budimansyah, Dasim; Komalasari, Kokom (Jurnal Ilmiah Peuradeun, 2022)
This paper aimed to analyze digital citizenship in civic education learning, focusing on the practice and implications of digital citizenship in civic education learning. This article provided a systematic review of 41 selected articles from the SCOPUS database of digital citizenship in civic education learning by analyzing content as a methodology for assessing the practice and implications of citizenship in civic education learning. The review identified the practice of digital citizenship in civic education learning from the dimensions of respecting, educating, and appreciating the practice of citizenship. The results of the literature review analysis revealed that the practice of digital citizenship is often used in political participation, democratic participation, citizen involvement, and being a citizen in the digital era. The implications of digital citizenship in civic education learning were still centered on materials such as politics, democracy, and citizen involvement. Another implication was that students, teachers, and curriculum are the most critical aspects of digital citizenship in the future. Some literature tries to carry out this study. Civic education is the central pillar in promoting digital citizenship in schools and the community.